The Influence of Financial Literacy, Consumptive Lifestyle, And E-Money on Family Financial Management in The Village of Tlogomas Malang City - Aristo Aldi; Elly Lestari; Moch Nurhidayat (International Research & Development for Human Beings (IRDH), 2026)
The aim of this study is to determine the effect of financial literacy, consumptive lifestyle and e-money on family financial management in RW 06, Tlogomas Village, Malang City, both partially and simultaneously. Descriptive research design, type of explanatory research using quantitative methods. The population of this research is a resident (head of the family) in the RW 06 environment of Malang City Tlogomas Village as many as 719, sampling techniques using purposive sampling obtained as many as 88 people. Instrument using a questionnaire. Data analysis uses multiple linear regression analysis. Hypothesis testing using the T (partial) test and F test (simultaneous). The results of multiple linear regression obtained by the three independent variables have a positive regression coefficient value and the coefficient of R Square's coefficient of 0.571 (contribution of the independent variable to the dependent variable of 57.1%). The results of the t (partial) hypothesis testing obtained the three independent variables have a tcount> ttable value significantly <0.05 and the results of the F (simultaneous) hypothesis testing obtained the Fcount> Ftable value with significantly <0.05. So it was concluded that financial literacy, consumptive lifestyle and e-money had a significant effect on family financial management in RW 06, Tlogomas Village, Malang City, both partially and simultaneously. The family should manage finances by considering the three factors of financial literacy, lifestyle, and e-money in order to achieve more stable and prosperous financial conditions.